Effectiveness of a multi-session combined near-peer and faculty-led surgical skills course on self-perceived ability to perform basic surgical skills. (September 2020) - Down, Billy; Morris, Simon; Kulkarni, Sagar; Mohiuddin, Kamran
Abstract: Background: Newly qualified UK doctors report feeling unprepared to perform basic practical procedures. The Royal College of Surgeons of England (RCSEng) responded to this concern by developing a national surgical curriculum, however, a national survey of UK medical schools identified that surgical skills teaching is inconsistent throughout the UK. Peer assisted teaching sessions are delivered by senior students to junior peers and have been demonstrated to be effective in a number of settings. We aimed to develop a peer-led surgical skills course for medical students and assess its efficacy in teaching surgical skills. Methods: Combined near-peer and faculty-led teaching sessions were delivered to medical students (N = 14). We assessed for confidence in these skills using pre- and post-course Likert scale questionnaires to determine self-perceived benefit. Results: Overall, student confidence in all skills improved by +1.254 (p < 0.0001). Individually, confidence in every skill increased significantly, including continuous suturing, knot tying and excision and closure, which improved by +1.45 (p < 0.001), +1.22 (p < 0.05) and +1.59 (p < 0.0001), respectively. Discussion: This study demonstrates that teaching provided through near-peer faculty improves medical student confidence in basic surgical skills. A similar course design could be implemented in other UK medical schools to improve the surgical skills of newly graduated doctors Highlights: This study shows an objective benefit to peer-led teaching surgical skills on undergraduate medical students' confidence. Near-peer learning is a beneficial process to students and teachers; equipping both with valuable skills and knowledge. Future medical curricula should consider incorporating near-peer style teaching in undergraduate surgical training. .